2023
DOI: 10.1021/acs.jafc.2c07090
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium longum CCFM1206 Promotes the Biotransformation of Glucoraphanin to Sulforaphane That Contributes to Amelioration of Dextran-Sulfate-Sodium-Induced Colitis in Mice

Abstract: Glucoraphanin, rich in broccoli seed extract (BSE), is generally inert but can be biotransformed into active sulforaphane by gut bacteria. This study aimed to screen probiotics with glucoraphanin-metabolizing ability and explore the effect of a combination of strain and BSE on colitis induced by dextran sulfate sodium (DSS) in mice. Bifidobacterium longum CCFM1206 was isolated from healthy adult feces. Ultra-high-performance liquid chromatography Q Exactive mass spectrometry analysis revealed the presence of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Similar to the findings from in vitro studies, broccoli has been reported to have anti-inflammatory, antioxidant, and prebiotic effects against IBD in animal models ( Table 2 [ 48 , 99 , 102 , 105 , 107 , 111 , 112 , 116 , 118 , 122 , 125 , [127] , [128] , [129] , [130] , [131] , [132] , [133] , [134] , [135] , [136] , [137] , [138] , [139] , [140] , [141] ] and Figure 1 ). Both the UC and CD models use chemical triggers or genetic knockouts.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar to the findings from in vitro studies, broccoli has been reported to have anti-inflammatory, antioxidant, and prebiotic effects against IBD in animal models ( Table 2 [ 48 , 99 , 102 , 105 , 107 , 111 , 112 , 116 , 118 , 122 , 125 , [127] , [128] , [129] , [130] , [131] , [132] , [133] , [134] , [135] , [136] , [137] , [138] , [139] , [140] , [141] ] and Figure 1 ). Both the UC and CD models use chemical triggers or genetic knockouts.…”
Section: Discussionsupporting
confidence: 74%
“… Cruciferous vegetables Image Bioactive compounds Preparation Dose Treatment period Pathways Benefits Model References purified SFN SFN purified compound 10, 20, and 40 mg/kg 14 d IL10 activation of STATs Anti-inflammatory DSS mice [ 118 ] purified SFN SFN purified compound 2.5, 5, 10 and 20 mg/kg 19 d IL6 and TNFɑ, STAT3 and Nrf2, Bifidobacterium and Lactobacillus spp. Prebiotic, Anti-inflammatory DSS mice [ 107 ] Broccoli SFN, GLR purified 600 ppm 4 wk IL1β and IL18, AMPK and PGC-1ɑ, Nrf2, HO-1, 8-OHdG Anti-inflammatory, Antioxidant DSS mice [ 127 ] SFN Raw and slightly cooked 10% (w/w) 2 wk IL6, CCR2, and VCAM-1 Anti-inflammatory DSS mice [ 128 ] GLR, ITCs Freeze-dried 4.1 mg/g 7 d NQO1 Antioxidant C57BL/6 mice [ 99 ] SFN Seed extract 370 mg/kg/d 2 wk Bifidobacterium spp., Nrf2 signaling Prebiotic, Anti-inflammatory DSS mice [ 129 ] Glucobrassicin Freeze-dried 15% (w/w) 24 d AHR, Cyp1a1, IL1β, IL10, IL6, Ptgs and CXCL5, increased Actinobacteria and Alistipes …”
Section: Discussionmentioning
confidence: 99%
“…20 A combination of Bifidobacterium longum CCMF1206 and broccoli seed extract (BSE) promotes the production of sulforaphane and sulforaphane- N -acetylcysteine in the feces of colitis mice, effectively activating the transcription and expression of Nrf2 pathway-related genes, leading to anti-inflammatory and antioxidative effects. 21 Bifidobacterium longum BL-10-encoded antioxidative genes demonstrate strong reducing and scavenging activities against DPPH, hydroxyl radicals, and superoxide anions. Oral administration can lower pro-inflammatory cytokines in mice with acute liver injury and mitigate liver damage symptoms through the regulation of the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…20 A combination of Bifidobacterium longum CCMF1206 and broccoli seed extract (BSE) promotes the production of sulforaphane and sulforaphane-N-acetylcysteine in the feces of colitis mice, effectively activating the transcription and expression of Nrf2 pathway-related genes, leading to anti-inflammatory and antioxidative effects. 21 Bifidobacterium longum BL-10-encoded antioxidative genes demonstrate strong reducing and scavenging…”
Section: The Impact Of Bifidobacterium Longum On the Cell Death Modal...mentioning
confidence: 99%
“…Likewise, members of Bacteroides have been shown to increase with broccoli consumption. [39,[71][72][73] Additionally, members of Bifidobacterium are known to increase with fiber consumption. [74] In fact, in vitro work has indicated that Bifidobacterium exclusively converts GLS into NITs.…”
Section: Discussionmentioning
confidence: 99%